2007
DOI: 10.2337/db06-1253
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Endoplasmic Reticulum Stress Gene Chop in Pancreatic Insulin-Producing Cells

Abstract: Endoplasmic reticulum stress-mediated apoptosis may play an important role in the destruction of pancreatic ␤-cells, thus contributing to the development of type 1 and type 2 diabetes. One of the regulators of endoplasmic reticulum stress-mediated cell death is the CCAAT/enhancer binding protein (C/EBP) homologous protein (Chop). We presently studied the molecular regulation of Chop expression in insulin-producing cells (INS-1E) in response to three pro-apoptotic and endoplasmic reticulum stress-inducing agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 54 publications
5
81
1
4
Order By: Relevance
“…This hypothesis is supported by the fact that Xbp1 knockdown had no effect on the expression of the ERstress markers Bip and Chop, the latter a transcription factor shown to be increased in beta cells under pro-apoptotic ERstress [15,19]. This is in line with previous studies showing that XBP1s is not required for normal development of islets [40] while it is essential to development of liver [35] and plasma cells [41].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This hypothesis is supported by the fact that Xbp1 knockdown had no effect on the expression of the ERstress markers Bip and Chop, the latter a transcription factor shown to be increased in beta cells under pro-apoptotic ERstress [15,19]. This is in line with previous studies showing that XBP1s is not required for normal development of islets [40] while it is essential to development of liver [35] and plasma cells [41].…”
Section: Discussionsupporting
confidence: 86%
“…The sarco/endoplasmic reticulum calcium ATPase-2 inhibitor, cyclopiazonic acid (CPA) (Sigma-Aldrich, Bornem, Belgium), which induces rapid depletion of ER Ca 2+ thus leading to ER-stress was dissolved in DMSO and used at a concentration of 25 μmol/l in beta cells and 50 μmol/l in 208F [2,19] Generation of recombinant adenoviruses and cell infection To produce XBP1 in insulin-secreting cells, we generated recombinant adenoviruses comprising fragments of the mouse Xbp1 (mXbp1) mRNA (gi|18139942|gb| AF443192.1) [20]. The following primers (Electronic supplementary material [ESM] Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cytokine-induced JNK activity is involved in b-cell apoptosis 7 and cytokineinduced CHOP expression in b-cells is regulated at least in part by JNK. 18 We performed a time-course analysis of IL-1b þ IFN-g-induced CHOP in the presence or absence of the chemical JNK inhibitor SP600125. 14 JNK inhibition partly, but significantly, hindered CHOP overexpression after 15 and 24 h of treatment, thus confirming that cytokineinduced CHOP overexpression is partly JNK-dependent (Supplementary Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a recent study has shown that in the Akita mouse model of diabetes, a mutation in Ins2 resulted in misfolding of the insulin protein causing ER stress and beta cell apoptosis [37]. Chronic exposure of islets and beta cells to fatty acids is known to cause dysfunction and cellular death [38], and this apoptosis has recently been shown to be the result of activation of an ER stress response [39][40][41]. Interestingly, ER stress markers have also been shown to be increased in islets from patients with type 2 diabetes [41,42], implicating ER stress as a contributor to beta cell dysfunction in humans.…”
Section: Possible Mechanisms That Could Explain Hypersecretion-inducementioning
confidence: 99%